Virtual play and the Victorian novel : the ethics and aesthetics of fictional experience - Gao, Timothy (Cambridge University Press, 2021)
Pondering the town he had invented in his novels, Anthony Trollope had 'so realised the place, and the people, and the facts' of Barset that 'the pavement of the city ways are familiar to my footsteps'. After his novels end, William Thackeray wonders where his characters now live, and misses their conversation. How can we understand the novel as a form of artificial reality? Timothy Gao proposes a history of virtual realities, stemming from the imaginary worlds created by novelists like Trollope, Thackeray, Charlotte Bronte, and Charles Dickens. Departing from established historical or didactic understandings of Victorian fiction, Virtual Play and the Victorian Novel recovers the period's fascination with imagined places, people, and facts. This text provides a short history of virtual experiences in literature, four studies of major novelists, and an innovative approach for scholars and students to interpret realist fictions and fictional realities from before the digital age.